RISK ASSESSMENT PERUSAHAAN EXPORT SEPATU PADA BAGIAN LINE UPPER PT. X - Novita Dewi Vebriyana Dankis; Mulyono Mulyono (Universitas Airlangga, 2015)
ABSTRACTRevolution in the industry sector has been rapidly grown to fill up all the needs of the consumer products. One involves supporting advanced machinery such as “Cutting, Skiving, Stitching, Emboss Logo, Roving, Punch Hole, Juki, BrushingEdge, Hammer Over Lapping and Two Molding”. In the factory production process, there are various types of high-risk activities, especially on line upper. The main of this research is to study the risk assessment on export companies line the upper part of the shoes export company using Job Safety Analysis. This research was conducted observational crosssectional design. Observations made to the hazards and control measures. Interviews were conducted to 12 employees. Variables in this research is production activity, hazard identification, risk assessment, risk control and residual risk. The results of hazard identification has been done, there are 91 known potential hazards, for risk assessment found 7 high risk and low risk 5. Machine classified as high risk on the risk assessment is roving machine, whereas low-risk is two molding machine. Control efforts on the upper line in accordance with the hierarchy of controlling a number of 91 controls, whereas for the residual risk still remains as much as 30 residual risk. Control has been applied quite well by pressing the consequences of hazards and risk management.Keywords: risk assessment, controlling, residual risk